COMPETITION ON THE WORLD STAGE: ANALYZING THE INFLUENCE OF THE UNITED STATES AND CHINA ON GLOBAL PROCESSES - Sadibakosev Khabibullo Shodiboy o‘gli (Western European Studies, 2023)
The 21st century is marked by a complex interplay of geopolitical forces, with the United States and China at the forefront of this global power dynamic. This article delves into the multifaceted competition between these two nations, examining their respective influences on global processes. We analyze the distinct approaches of the United States, characterized by its long-standing global leadership and promotion of liberal values, and China, with its rapidly expanding economic and geopolitical clout, often challenging the existing world order. The study explores the competition across various dimensions, including economic influence through trade and investment, military power projection, technological innovation, and the struggle for ideological dominance. We investigate how this rivalry impacts critical global issues such as climate change, global health governance, and international security. By dissecting the strategies employed by both nations, this article provides insights into the potential trajectories of this power competition and its implications for the future of the international system. Understanding the nuances of this rivalry is crucial for policymakers, scholars, and anyone invested in navigating the complexities of the 21st-century world order
Keywords: United States; China; global competition